Red at the bone [large type] - Woodson, Jacqueline (Random House Large Print, 2019)
As the book opens in 2001, it is the evening of sixteen-year-old Melody's coming of age ceremony in her grandparents' Brooklyn brownstone. Watched lovingly by her relatives and friends, making her entrance to the music of Prince, she wears a special custom-made dress. But the event is not without poignancy. Sixteen years earlier, that very dress was measured and sewn for a different wearer: Melody's mother, for her own ceremony-- a celebration that ultimately never took place. Unfurling the history of Melody's parents and grandparents to show how they all arrived at this moment, Woodson considers not just their ambitions and successes but also the costs, the tolls they've paid for striving to overcome expectations and escape the pull of history. As it explores sexual desire and identity, ambition, gentrification, education, class and status, and the life-altering facts of parenthood, Red at the Bone most strikingly looks at the ways in which young people must so often make long-lasting decisions about their lives--even before they have begun to figure out who they are and what they want to be.